Corporate parenting in a pandemic: Considering the delivery and receipt of support to care leavers in Wales during Covid-19. (September 2021) - Roberts, Louise; Rees, Alyson; Mannay, Dawn; Bayfield, Hannah; Corliss, Cindy; Diaz, Clive; Vaughan, Rachael
Highlights: During COVID-19, care leavers in Wales looked to their corporate parents for support. Social care workers sought to provide continued support despite lockdown restrictions. Some young people felt supported, but others felt neglected and forgotten. Corporate parenting responses had the potential to mitigate or compound adversities during COVID-19. Evidence from this study supports on-going efforts in Wales to strengthen corporate parenting. Abstract: This paper considers the support available to care leavers during the Covid-19 pandemic from their corporate parents. The paper contributes to a developing evidence base concerned with social work efforts to adapt and maintain support provision during the unprecedented circumstances, and provides insight into how such support was perceived and experienced. Funded by Voices from Care Cymru and Cardiff University, a qualitative, mixed method study was conducted which included a survey of Welsh Local Authority professionals (n = 22) and interviews with Welsh care-experienced young people aged 17–24 (n = 17). The findings of this paper show the propensity of corporate parents to provide protection against the adversities of the pandemic, or to compound difficulties. While some young people reported being both practically and emotionally supported, for others corporate parenting support was perceived as unavailable, unhelpful and / or uncaring. The Covid-19 pandemic provides a unique lens to consider the strengths, flaws and future opportunities for corporate parenting. The findings emphasise the need for parity of support for young people leaving care and consideration of national, local and individual responses is included. Yet consistent with findings pre-dating the pandemic, the findings reaffirm the enduring importance of both relationships and resources in ensuring good support for care leavers.